Analiza porównawcza funkcji nazw własnych postaci w powieści Terry’ego Pratchetta Men At Arms i jej polskim tłumaczeniu Zbrojni - Gibka, Martyna (Papers in Linguistics, 2019)
The article is devoted to a comparative analysis of the functions served by proper names of the characters in the second part of the City Watch Cycle by Terry Pratchett and in the Polish translation of this novel. Its main aim is to examine what happens with the functions served in the original and in the translation. Are they preserved, lost, changed or added? Moreover, the reasons for the changes are identified. The analysis is based on the theory of two acts (proposed in 2017), which divides the functions into two groups: permanent and temporary.